Net neutrality at internet backbone provider level - Laura Baglioni; Armando Calabrese; Nathan Levialdi Ghiron (International Telecommunications Society (ITS), 2013)
This paper analysis the Internet interconnection market and combine the main technical (i.e. service quality) and economic aspects (i.e. profits and utility) characterizing relations between market players (end users, EUs; Internet Service Providers, ISPs; Internet Backbone Providers, IBPs) in order to determine possible economic outcomes in the strategic interaction between them. The proposed model enables a comparison to be made between expected values of social welfare (i.e. EU utility and profits of both ISPs and IBPs) on the current scenario (Best Effort) and considering two classes of priority in the traffic routing. Finally we illustrate the model's applicability to an example of network.
Keywords: 330; Net Neutrality; pricing; competition; service quality; Internet interconnection